Cooperative Strategies: evaluating network strategy management of small and medium-sized enterprises - Bortolaso, Ingridi; Verschoore, Jorge Renato; Antunes Júnior, José Antônio Valle (Review of Business Management, 2012)
Network formation aiming the development of cooperation among small and medium-sized companies has received increasing interest from the organizational field. Recent studies have been devoted to understand the management of those networks, deepening the collective aspects of the structure, the coordination, and the processes, among others. This article lies within the context of network strategy management progress and tries to understand how cooperative strategies are developed and executed. Its main objective is to evaluate to what degree the cooperative strategies in networks of small and mid-sized firms are developed. The study was based on the theoretical evaluation of networks proposed by Bortolaso et al. (2010) and addressed different aspects of cooperative strategy management in those networks, like i) the definition of common strategic objectives, ii) the collective analysis of the environment, iii) strategic network planning, iv) the deployment of the strategy in joint actions, v) monitoring of strategic planning by means of regular meetings and vi) the establishment of collective performance indicators. To achieve those goals, our analysis focuses on cooperation networks in the State of Rio Grande do Sul, Brazil, which has already established over 200 small and mid-sized enterprise networks with the support of a public policy. To carry out our study, we visited 12 networks and conducted 60 interviews, i.e., five per network. The network evaluation results show that cooperative strategies are still at a low stage of development. Among the evaluated networks, only four of them feature more developed cooperative strategies. Based on these results, we performed detailed analyses of the seven aspects mentioned above, as well as a consolidated evaluation of the development level of the cooperative strategy of the networks, totalizing eight analyses. This article also points out how networks could be improved and highlights avenues for further research. Key words: Cooperation. Networks. Small and mid-sized firms. Cooperative strategies.